2023
DOI: 10.1111/bph.16036
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of alantolactone as a naturally occurring NLRP3 inhibitor to alleviate NLRP3‐driven inflammatory diseases in mice

Abstract: Background and Purpose: The NLR family pyrin domain-containing 3 (NLRP3) inflammasome is activated in many inflammatory conditions. So far, no low MW compounds inhibiting NLRP3 have entered clinical use. Identification of naturally occurring NLRP3 inhibitors may be beneficial to the design and development of compounds targeting NLRP3. Alantolactone is a phytochemical from a traditional Chinese medicinal plant with anti-inflammatory activity, but its precise target remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Drug affinity responsive target stability (DARTS) assay is a common technique for the determination of drug targets. , The binding of small molecule drugs to their target proteins will reduce the sensitivity to degradation caused by pronase. In order to explore whether the direct interaction between J27 and JNK2 is specific, we used DARTS to detect the binding ability of J27 to JNK1 and JNK3.…”
Section: Resultsmentioning
confidence: 99%
“…Drug affinity responsive target stability (DARTS) assay is a common technique for the determination of drug targets. , The binding of small molecule drugs to their target proteins will reduce the sensitivity to degradation caused by pronase. In order to explore whether the direct interaction between J27 and JNK2 is specific, we used DARTS to detect the binding ability of J27 to JNK1 and JNK3.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, we have yet to further investigate the target of Ala. Recent study has shown that Ala inhibits NLRP3 inflammasome activity by directly targeting the NACHT domain of NLRP3 [ 33 ]. In addition, Ala plays an anti-inflammatory role in LPS-stimulated RAW 264.7 cells by inhibiting NF-κB activation and MAPKs phosphorylation through down-regulating MyD88 signaling pathway [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSDMD, the representative indicator of pyroptosis, which is also a substrate of caspase-1, and its escaped N-terminal fragment, subsequently localizes and oligomerizes within the plasma membrane to form a pore, providing an exit for bioactive IL-1β and IL-18. 33 Pyroptotic cell death of pulmonary macrophages is one of the key pathological mechanisms of LPS- and cardiopulmonary bypass (CPB)-induced acute lung injury, 6 , 34 both of which could be alleviated by EA administration. 35 Therefore, we evaluate the effect of EA pretreatment on the release of IL-1β and IL-18 in lung tissue of CpG-challenged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis occurring in pulmonary macrophages plays a crucial role in acute lung injury, and this process can be principally triggered by inflammasome activation. 6 Inflammasomes are intracellular platforms containing cytosolic pattern recognition receptors, among which nucleotide-binding oligomerization domain-like receptor pyrin domain containing 3 (NLRP3) is the most in-depth studied and clinically implicated one. 7 , 8 Purinergic CD39 functions as hydrolyzing ATP, the accumulation of which mediates NLRP3 activation and further controls the maturation of IL-1β and IL-18.…”
Section: Introductionmentioning
confidence: 99%